Ovarian microbiota and ovarian cancer: An overview and update meta-analysis - Di Donna, Mariano Catello; Cucinella, Giuseppe; Solazzo, Maria Cristina; Capozzi, Vito Andrea; Rotondella, Isabella; Etrusco, Andrea; Laganà, Antonio Simone; Ronsini , Carlo; Scarpelli, Elisa; Romeo, Paola; Palmara, Vittorio; Cianci, Stefano; et al. (Acta Biomedica Atenei Parmensis, 2025)
Background: Ovarian cancer (OC) remains the most lethal gynecological malignancy, although advancements in treatment strategies. Emerging data suggested the potential role of ovarian microbiota in ovarian cancer pathogenesis. The objective of this review and meta-analysis is to analyze available literature to investigate this correlation. Methods: According to the recommendations in the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement, the Pubmed database and the Embase database were searched in February 2024. No limitation of the countries was considered. Results: Twenty-seven studies met the inclusion criteria. Five thousand and fourteen ovarian carcinoma cases were included of which 1659 (33.1%) showed dysbiosis. The fixed-effect model and the random-effect model showed no significant correlation between ovarian cancer patients and dysbiosis (p<0.001 and p<0.001 with 95% Confidence Interval 0.21-0.35 and effect size 0.28, respectively). The heterogeneity between studies was high with an I2 of 95.76% (p<0.001). Conclusions: Our meta-analysis suggests no significant difference in dysbiosis prevalence between OC patients and controls. Considering the substantial heterogeneity found, more studies with control groups and precise methodologies are needed to further evaluate the potential role of the ovarian microbiota in the OC.